La menorà: culto, storia e mito = The menorah. Cult, history and myth - Leone, Francesco; Nesselrath, Arnold; Di Castro, Alessandra (Skira, 2017)
Published on the occasion of the exhibition 'The Menorah: worship, history and myth', in collaboration with the Vatican Museums and the Jewish Community of Rome, held at the Braccio di Carlo Magno within the Vatican, and at the Jewish Museum of Rome, the volume retraces the compelling millenary history of the Menorah: the legendary pure gold candelabrum forged by Moses under the guidance of God, safeguarded within the Temple of Jerusalem, which through time has become the symbol of the Jewish People, whose form was copied in mediaeval times, as a seven-armed candlestick used liturgically in Christian churches. Over 400 pages, rich in introductory texts in Italian and English, as well as the reproduction in color of all the 130 works of art on display - masterpieces from the history of art from archeology to contemporary times - antique sculptures, antique glassware, paintings from artists such as Giulio Romano, Andrea Sacchi, Nicolas Poussin and Marc Chagall, manuscripts, imposing Christian candelabra dating from the XIII to the XVIII century, roman baroque silver, illuminated manuscripts of worldwide importance such as the Bible of St. Paul, from the Carolingian period